Hemp hurds biorefining: A path to green l-(+)-lactic acid production. (September 2015) - Gandolfi, Stefano; Pistone, Lucia; Ottolina, Gianluca; Xu, Ping; Riva, Sergio
Highlights: Hemp hurds were subjected to mild organosolv pretreatment and enzymatic hydrolysis. High yields of fermentable carbohydrates (C5 and C6) and lignin were obtained. No detoxification step before fermentation of sugar was required. Lignocellulosic sugars were fermented tol -lactic acid by Bacillus coagulans XZL4. Lactic acid titers were 109 g/L from C5 and 141 g/L from C6. Abstract: Sugars streams generated by organosolv pretreatment of hemp hurds, cellulose (C6) and hemicellulose (C5) fractions, were fermented to lactic acid (LA) by Bacillus coagulans strains XZL4 and DSM1. Pretreatment conditions and enzymatic hydrolysis were optimized and B. coagulans aptness to use lignocellulosic-derived sugars as a carbon source was evaluated. Methanolic organosolv pretreatment with 2.5% (w/w) H2 SO4 gave the best results in terms of glucan recovery (98%), enzymatic hydrolysis of pretreated biomass (70%) and hemicellulosic sugars recovery (61%). C6 and C5 sugars fermentation by strain XZL4 gave, high LA yields (0.90 and 0.84 g/g), high titers (141 and 109 g/L), and high enantiomeric excess (>99%). Overall, 42 g ofl -LA were obtained from 100 g of raw hemp hurds. These results can be considered promising for lignocellulosic feedstock valorization toward the production of polymer-grade LA.